VD_FINDINFO Décision / 2015 / 769 vom 19. Oktober 2015 - VD Tribunal cantonal (2015)
CLASSEMENT DE LA PROCÉDURE, VIOL, INTÉGRITÉ SEXUELLE, FRAISEN GÉNÉRAL | 190 CP, 136 CPP (CH), 138 CPP (CH), 319 CPP (CH), 420 CPP